Biodiversity, Antimicrobial Potential, and Phylogenetic Placement of an Endophytic Fusarium oxysporum NFX 06 Isolated from Nothapodytes foetida. (22nd December 2013) - Musavi, Sogra Fathima; Balakrishnan, Raj Mohan
Abstract : Biodiversity of endophytic fungi associated with the medicinal plant Nothapodytes foetida of Agumbe forest was determined and evaluated for its microbial activity. A total of 170 endophytic isolates were obtained from leaf, stem, seed, and fruit tissues of Nothapodytes foetida . The dominant endophytic fungi belong to genera Fusarium, Penicillium, Aspergillus, and Colletotrichum . Maximum endophytic isolates were obtained from leaves segments followed by fruit, stem, and seed tissues. Hyphomycetes were the dominant group found with 75.29% over other fungal groups. Shannon-Weiner and Simpson indexes showed rich diversity of endophytic fungi suggesting even and uniform occurrence of various species. 88.57%, 74.28%, 62.85%, and 65.71% of isolates have shown activity against Staphylococcus aureus (ATCC 25923), Pseudomonas aeruginosa (ATCC 27853), Escherichia coli (ATCC 25922), and Candida albicans (ATCC 69548), respectively. One of the isolate NFX 06 isolated from leaf has showed considerable antimicrobial activity against all the test pathogens. It was identified as Fusarium oxysporum by ITS sequence analysis; the nucleotide sequence was submitted in the GenBank with an accession number KC914432. Phylogenetic relationship confirmed that the strain F. oxysporum NFX 06 has evolved from an endophytic ancestor.